Bradycardic effects mediated by activation of G protein-coupled estrogen receptor (GPER) in rat nucleus ambiguus - Brailoiu, G. Cristina (2012)
G protein-coupled estrogen receptor (GPER) has been identified in several brain regions including cholinergic neurons of nucleus ambiguus, which are critical for the parasympathetic cardiac regulation. Using calcium imaging and electrophysiological techniques, microinjection into nucleus ambiguus and blood pressure measurement we examined the in vitro and in vivo effects of GPER activation in nucleus ambiguus neurons. G-1, a GPER selective agonist, produced a sustained increase in cytosolic Ca(2+) concentration in a concentration-dependent manner in retrogradely-labeled cardiac vagal neurons of nucleus ambiguus. The increase in cytosolic Ca(2+) produced by G-1 was abolished by pretreatment with G36, a GPER antagonist. G-1 depolarized cultured cardiac vagal neurons of nucleus ambiguus. The excitatory effect of G-1 was also identified by whole-cell visual patch-clamp recordings in nucleus ambiguus neurons, in medullary slices. To validate the physiological relevance of our in vitro studies, we carried out in vivo experiments. Microinjection of G-1 into the nucleus ambiguus elicited a decrease in heart rate; the effect was blocked by prior microinjection of G36. Systemic injection of G-1, in addition to a previously reported decrease in blood pressure, also reduced the heart rate. The G-1-induced bradycardia was prevented by systemic injection of atropine, a muscarinic antagonist, or by bilateral microinjection of G36 into the nucleus ambiguus. Our results indicate that GPER-mediated bradycardia occurs via activation of cardiac parasympathetic neurons of the nucleus ambiguus and support the involvement of GPER in the modulation of cardiac vagal tone.